2020
DOI: 10.1039/c9tb02439e
|View full text |Cite
|
Sign up to set email alerts
|

Boosting biomolecular interactions through DNA origami nano-tailored biosensing interfaces

Abstract: Nano-tailored DNA origami designs nanostructure the bioreceptor layer of encoded microparticles in an innovative microfluidic platform, hereby boosting biomolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…(Fig. 4) could contribute to overcoming labour-intensive and time-consuming approaches in biosensing, leading to the development of a new generation of specific, rapid, and high-throughput analytical platforms [72].…”
Section: Origami-based Structure Design and Mechanismsmentioning
confidence: 99%
“…(Fig. 4) could contribute to overcoming labour-intensive and time-consuming approaches in biosensing, leading to the development of a new generation of specific, rapid, and high-throughput analytical platforms [72].…”
Section: Origami-based Structure Design and Mechanismsmentioning
confidence: 99%
“…Therefore, there is a continuous need for improvement and development of more efficient tools. DNA origami-based technology has the potential to revolutionize the development of a new generation of highly specific, fast, high throughput analytical devices with a single-molecule sensitivity for bio-medical applications [21,42,43].…”
Section: Dna Origami-based Structures Used For Biomolecular Sensingmentioning
confidence: 99%
“…Many approaches use fluorophores within immunoassays to improve the assay sensitivity, required for early disease detection (i.e., when the disease is still asymptomatic). A recent article by Rutten et al [43], reported a bioassay to detect thrombin in only 25 min consisting of a DNA origami structure labeled with aptamers and fluorophores with a LOD of 2 ± 0.2 nM. Chen et al [70] developed a sensor using an alternative DNA origami method called DNA nanoribbons.…”
Section: Fluorescence-based Sensorsmentioning
confidence: 99%
“…18 Rutten et al has recently reported a unique scaffold, 3D DNA origami design, consisting of a 24-helix cylindrical bundle with ssDNA elongations on the side for DNA-mediated receptor coupling, and of a biotin-containing at the terminal region for coupling to the streptavidin-mediated microparticles surface. 19 It has a stable structure (up to 50 °C, pH 10), but the design of the 3D DNA origami structure is complicated. Furthermore, the DNA aptamers are immobilized on the sides of the cylindrical bundle, so they cannot be displayed vertically to the sensor surfaces.…”
Section: Introductionmentioning
confidence: 99%